1994
DOI: 10.1002/1097-0142(19940915)74:6<1746::aid-cncr2820740617>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between microscopic margins of resection and the risk of local recurrence in patients with breast cancer treated with breast-conserving surgery and radiation therapy

Abstract: Background. The relationships among the involvement of tumor at the final margins of resection, the presence of an extensive intraductal component (EIC), and the risk of local recurrence are important considerations in patients treated with conservative surgery and radiation therapy for early stage breast cancer but have not been defined adequately. Methods. Between 1982 and 1985, 885 patients were treated for clinical Stage I or II invasive breast cancer. The study population was limited to 181 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
168
2
11

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 441 publications
(190 citation statements)
references
References 14 publications
9
168
2
11
Order By: Relevance
“…87,88 Most recently, the EORTC has reported the favorable impact of boost on local failure rates. 88 Several considerations may be involved in the decision to use a boost: histological studies show that residual cancer following resection of the primary cancer usually is in the vicinity of the primary site; 89 recurrences following treatment usually are seen at or near the primary site; 90 and boost treatment can be delivered without significant morbidity. 91 Although boost irradiation generally is used, the precise indications for its use are not well defined.…”
Section: Elements In the Technique Of Irradiationmentioning
confidence: 77%
“…87,88 Most recently, the EORTC has reported the favorable impact of boost on local failure rates. 88 Several considerations may be involved in the decision to use a boost: histological studies show that residual cancer following resection of the primary cancer usually is in the vicinity of the primary site; 89 recurrences following treatment usually are seen at or near the primary site; 90 and boost treatment can be delivered without significant morbidity. 91 Although boost irradiation generally is used, the precise indications for its use are not well defined.…”
Section: Elements In the Technique Of Irradiationmentioning
confidence: 77%
“…Certainly, other authors have shown that DCIS in core biopsies is a marker of extensive intraductal component, 9,10 a previous relative contraindication for breast conservation, [20][21][22] which had been considered to increase the risk of compromised margins. 23,24 In this study, a DCIS component on core biopsy was associated with extratumoural DCIS on excision specimen. This relationship appeared particularly pronounced in patients who had a high percentage of DCIS on core biopsy, with 57% of patients with extratumoural DCIS having 450% DCIS component on core biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…11,[42][43][44] Consistent with these reports, in the study reported here, the presence of negative margins was associated with improved IBTR-free survival in both univariate and multivariate analyses. Therefore, our multidisciplinary emphasis on improving margin status may have contributed to the declining IBTR rates in our study.…”
Section: Discussionmentioning
confidence: 99%